Efeitos da fotobiomodulação sistemica utilizando led e laser sobre a resposta sensorio-motora na lesão nervosa periférica em ratos wistar - Araujo, Tamires Ribeiro de (2021)
Introduction: Peripheral Nerve Injury (PNI) are injuries that cause great functional damage. A feature of photobiomodulation (PBM) that has been explored as an aid to the treatment of PNI is systemic PBM (SPBM), which has already demonstrated positive effects in other clinical conditions including, reduction of the inflammatory process and increase in the production of ATP. Objective: To compare the effects of SPBM with LLT and LED after PNI on motricity, sensitivity and muscle morphology. Methodology: Wistar rats distributed in 4 groups, control, Lesion, SPBM-LED and SPBM-LLT, were used. The PNI occurred through the sciatic nerve crushing technique and treatment with SPBM-LED (850nm, 40mW, 3.2J) and SPBM-LLT (780nm, 40mW, 3.2J), administered in the animal's tail region. Assessments were made using the Functional Sciatic Index (FSI), von Frey test and the right and left anterior tibial muscles were collected for analysis of muscle and histological mass by Hematoxylin & Eosin (HE) staining with 7, 14 and 21 days after injury. Results: The FSI showed functional improvement in the SPBM-LLLT group in all periods, there was pain reduction with 14 days in the von frey test in the FBMS-LBI group, the L/R ratio showed a reduction in muscle atrophy in the FBMS-LBI group at 7 days, the diameter of the muscle fiber showed an increase in the SPBM-LED group at 14 days and there was an increase in the cross-section area (CSA) in the SPBM-LED and SPBM-LLT groups at 7 days. Conclusion: The SPBM-LLT using both light sources, LED and LLLT, using the neuromuscular recovery after LNP to positively modulate the results being enhanced in the groups treated with LLLT.